Testemunhos desde a ferida: travessias para além da violência - Camargo, Karina Acosta (2023)
This research crosses the issues of testimony, through the fissures in the researcher's own flesh, due to sexual abuse experienced during childhood. Testimonies from the wound consists of a way of saying and an art of telling from an unusual place: the wound. Based on it, the present research aims to go beyond the victim-aggressor dichotomy. Without attributing violence exclusively to a subject, one tries to think about abusive practices beyond and below the subjects, managed in and by the social field. In this trajectory, the research undergoes a process of dismantling: it is crossed by confrontations, paralysis and interruptions, becoming an evaluation of what a thought can think beyond the State, the official language, and the practices of power and dominant knowledge. Between the texture of pain and the unspeakable, the power of the intimate – freed from a particular and private dimension – makes itsel on the process of creation of an open word, in a living and extrapersonal silence. Thus, fragmentary, partial and open writing and listening become an ethics. Along this path, this research became a minor thesis, in which a becoming-minor of thought is exercised as an active force and a body stitched together by testimonial lines remakes itself through crossings through the wound, inaugurating another time towards beyond violence